Allelopathic Effects of Poplar (Populus deltoides Bartr. Ex Marsh): An Assessment on the Response of Wheat Varieties under Laboratory and Field Conditions - Nandal, D.P.S.; Dhillon, A. (Indian Journal of Agroforestry, 2020)
A field experiment with ten wheat varieties (UP-2338, HO-2687, WH-147, WH-283, WH-542, WH-157, HO-2329, PBW- 343, WH-896, WH-533) under four and a half years old poplar trees at a spacings of 5 m x 4 m, 10 m x 2.5 m , 15 m x 2.5 m and germination studies with three poplar leaf extract concentrations of 5, 10, and 20 per cent was carried out at CCS Haryana Agricultural University, Hisar (India) during 1999-2000. Wheat variety, WH-896 out yielded all other wheat varieties except WH-542 at all the spacings of poplar. The germination of WH-896, WH-157 and HO-2329 wheat varieties remained unaffected at all the extracts of poplar leaves. Similarly shoot length of all varieties except UP-2338, HO-2687, WH-147 and WH-157 remained unaffected at all extract concentrations. Based on the studies, wheat varieties WH-896 and WH-542 showing tolerance to poplar allelochemicals as well as less effect of other poplar influences are suggested for cultivation with poplar.